Pelestarian tulisan Jawi-Manifestasi seni khat Islami di masjid-masjid negeri Perak - Ahmad@Lubis Mohamad Bohari, Mohd Radzi Idris, Al Muhsin Muhammad Anas (Universiti Pendidikan Sultan Idris, 2004)
Pelestarian tulisan Jawi-Manifestasi seni khat Islami di masjid-masjid negeri Perak by Ahmad@Lubis Mohamad Bohari, Mohd Radzi Idris, Al Muhsin Muhammad Anas,